The looking after children in Scotland materials - Jane Scott; Malcolm Hill (Scottish Journal of Residential Child Care)
The Looking After Children materials provide a comprehensive aid for planning and participation to help ensure the physical, emotional and social needs of young people in residential care. They comprise 2 sets of forms, recording essential information, plans and reviews, and assessment and action. They were adapted to Scottish context and legislation and piloted in 1997-8. Broad principles were welcomed, but usage only partial. By 2004 30 of 32 Scottish local authority social work departments had adopted all or part of the system. Reports on a survey in 2002-3 assessing how the materials were used in practice. Questionnaires were sent to local authorities; 19 (59%) were returned. Results described the organisational context; training and preparation; experience of use; information, care planning and review forms; assessment and action records; experience with other agencies; IT systems; implications for the residential care of young people; and the wider context and implications. Concludes that much creativity and imagination has been invested in implementation and training strategies for this first national system enabling the development of looked after children and young people to be recorded and followed, and a wealth of knowledge and practical advice shared. Difficulties remaining include time and resource constraints, and a need to engage staff more fully in communication.